The place of alternative energy sources in the field of architecture - Asylbekov K.T., Асылбеков К.Т. (Рroblems of engineering and professional education, 2023)
The article is devoted to alternative energy sources and their role in the field of architecture. The results of the study showed all the benefits of using groundwater, solar and wind energy. As a result of the study, a number of proposals were made